The Relationship between Demographic-Obstetrics Variables and Quantitative Adequacy Index of Prenatal Care with Preeclampsia - Maryam Moradi; Azin Niazi; Farzaneh Salajegheh Tezerji; Fatemeh Zahra Karimi; Seyedeh Azam Pourhoseini; Ehsan Mazloumi (Mashhad University of Medical Sciences, 2024)
Background: Preeclampsia is one high blood pressure (hypertension) disorder occurring during pregnancy with adverse effects on both mother and fetus.Aim: The present study was performed with aim to determine the relationship between demographic-obstetrics variables and quantitative adequacy index of prenatal care with preeclampsia.Method: This case-control study was performed on 90 preeclampsia and 150 non-preeclampsia women referred to the university hospitals in Mashhad. The samples in the case group were selected from the hospitalized individuals with a definite diagnosis of preeclampsia, and those in the control group among pregnant women without preeclampsia referred to receive prenatal care. Data were analyzed by SPSS software (version 22). P<0.05 was considered statistically significant.Results: The prevalence of preeclampsia was 2 times in women with a history of infertility. Also, 13.3% of women with preeclampsia had anemia (p=0.026), 4.4% had a history of chronic hypertension and the odds of developing preeclampsia in these women was 16 times. The women with preeclampsia received 50% inadequate care, which was 47.2% in the control group.Implications for Practice: Age, body mass index, maternal pre-pregnancy weight, LMP-based gestational age, multiple births, nulliparity, first pregnancy of current spouse, history of infertility and use of assisted reproductive technology, chronic hypertension and history of preeclampsia in individual and first grade relatives, and inadequate prenatal care were the risk factors for preeclampsia. Planning to moderate risk factors, early identification of high-risk individuals, and adequate prenatal care coverage should be considered by healthcare providers to decrease the complications of preeclampsia.